INSILICO QSAR AND MOLECULAR DOCKING STUDIES OF SELECTED MEDICINAL PLANT COMPOUNDS AGAINST NS5 & NS3 PROTEIN OF DENGUE VIRUS: A COMPARATIVE APPROACH - SUGANYA. J; RADHA MAHENDRAN (International Journal of Pharma and Bio Sciences, 2016)
Dengue fever is the most common mosquito transmitted viral infection affecting 2.5 billion people throughout the world. Previously, several studies have reported that NS5 & NS3 are potential targets against dengue virus. Design and synthesis of novel plant compounds have become an important aspect in the field of drug discovery. Hence we have made an attempt to design computationally drugs against dengue virus using novel plant compounds. QSAR and docking studies were performed on 75 medicinal plant compounds. QSAR studies revealed 11 inhibitory molecules against NS5 and 8 inhibitory molecules against NS3. Docking studies revealed 13 inhibitory molecules against NS5 and 3 inhibitory molecules against NS3.On Comparative analysis between the QSAR and docking results, 3 compounds for NS5 & 2 compounds for NS3 were found to be best inhibitory molecules. Further, these compounds could be useful for the identification and development of new preventive and therapeutic drug against dengue virus.